Thirteenth annual pezcoller symposium: Focusing analytical tools on complexity in cancer - MIHICH, Enrico; FEUNTEUN, Jean; FRIEND, Stephen (Cancer research (Chicago, Ill.), 2002)
The physiopathology of cancer cells is the result of very complex signaling networks that represent in many cases distortions of the orderly networks regulating the physiology of normal cells. These networks are the consequence of the expression of, or the lack of expression of, genes, mutated or not, which represent the genomic profile of different types of or of individual cancers. The complex signaling pathways, the cross-talks among them, and the redundancies existing for several of them mediate not only the transmission of signals from the cell environment to the nucleus but also that from the nucleus to the other cellular components whose function is involved in cell proliferation, apoptosis, or differentiation. Modern approaches to cancer therapy and also prevention are aimed at identifying new molecular targets, pivotal to the life of the cancer cell, which would provide for specific sites of intervention. In the face of the enormous complexity of the phenomena on which the life of cancer cells is based, it is both difficult to identify unique specific target for intervention and important to develop analytical tools and approaches capable to identify them for further exploitation. This was the main subject of the Symposium. Consideration was given to: (a) tumor genotypic analysis through expression array evaluation and definition of cancer transcriptomes in studies aimed at identifying determinants of specific characteristics of cancer cells; (b) approaches based on the knowledge gained in this analysis that would lead to the visualization of new targets exploitable for antitumor action; and (c) multifactorial analysis of the complex interactions regulating cancer cells and methods to comprehend the complexity of molecular models and validate their functional relevance.